Prevalence of Gastrointestinal Parasite on Cats in Shelter East Surabaya - Akbar Wijaya Putra Purnama; Lucia Tri Suwanti; Hani Plumeriastuti; Endang Suprihati; Kusnoto Kusnoto; Agus Sunarso (Universitas Airlangga, 2019)
The purpose of this study was to determine the prevalence of gastrointesatinal parasites in cats at Surabaya shelter. Eighty two samples of cat feces used in this study were taken from Griya satwa shelter and Kiro cat shelter. Feces samples were examined using the native, sedimentation and floating methods. Feces samples gastrointestinal parasite were identified by using a microscope with 400x and 1000x magnifications. Faces samples that are diagnosed positively if there is at least one of the three methods. Feces samples has observed, obtained prevalence rate of 43.9% or 36 positive samples from eighty two samples. The results of chi square analysis showed that p > 0.05, which showed that the parasites taken in the two shelters had clear differences in the prevalence of the gastrointestinal tract parasites. The parasites observed were Isospora sp., Ancylostoma sp., Toxocara cati and Toxocara leonina.